Removal of Non-Steroidal Anti-Inflammatory Drugs from Aqueous Environments with Reusable Ionic-Liquid-based Systems - Almeida, Hugo F. D. (ACS Sustain Chem Eng, 2017)
In the current era of human life, we have been facing an increased consumption of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). Nevertheless, NSAIDs are not completely metabolized by humans and are further excreted into domestical effluents. Several studies have been showing that a wide variety of pharmaceuticals are present in water effluents and are thus a matter of serious concern in the public health. Although treatment plants use sophisticated technologies for pollutants/contaminants removal, none of these processes was particularly designed for NSAIDs. In this perspective, this work addresses the use of a liquid-liquid extraction approach, employing ionic liquids (ILs), for the removal of NSAIDs from aqueous media. In particular, aqueous biphasic systems (ABS) composed of ILs and aluminium-based salts, which are already used in water treatment plants, were tested for the removal of diclofenac, ibuprofen, naproxen and ketoprofen. With these systems, extraction efficiencies of NSAIDs up to 100% were obtained in a single-step. The recovery of NSAIDs from the IL medium and the recyclability of the IL-rich phase were then ascertained to guarantee the development of a more sustainable and cost-effective strategy. Based on the remarkable increase in the solubility of NSAIDs in the IL-rich phase (from a 300- to a 4100-fold when compared with pure water), water was then studied as an effective anti-solvent, and where single-step recovery percentages of NSAIDs from the IL-rich phase up to 91% were obtained. After the “cleaning” of the IL-rich phase by the induced precipitation of NSAIDs, the phase-forming components were recovered and reused in four consecutive cycles, with no detected losses on both the extraction efficiency and recovery of NSAIDs by induced precipitation. Finally, an integrated process is here proposed, which comprises the (i) removal of NSAIDs from aqueous media, (ii) the cleaning of the IL-rich phase by the recovery of NSAIDs by induced precipitation, and (iii) the phase-forming components recycling and reuse, aiming at unlocking new doors for alternative treatment strategies of aqueous environments.